CLINICAL AND PROGNOSTIC FEATURES OF CHRONIC CRITICAL ILLNESS/PERSISTENT INFLAMMATION IMMUNOSUPPRESSION AND CATABOLISM PATIENTS: A PROSPECTIVE OBSERVATIONAL CLINICAL STUDY. Issue 1 (17th January 2023) - Zhou, Qingqing; Qian, Hebu; Yang, Aixiang; Lu, Jian; Liu, Jun
ABSTRACT: Objective: The aims of this study were to investigate and compare the clinical features and prognosis of chronic critical illness (CCI)/persistent inflammation immunosuppression and catabolism (PICS). Methods: This is a prospective observational clinical study. During this study period, we collect intensive care unit patients' data from Suzhou Municipal Hospital and Suzhou Ninth People's Hospital. All patients older than 18 years were included, and according to the corresponding exclusion and diagnostic criteria, they were divided into four groups: PICS group, CCI group, CCI and PICS group (CCI + PICS), and neither CCI nor PICS group (NCCI + NPICS) and collected and recorded age, sex, hospital time, hospital diagnosis, Acute Physiology and Chronic Health Evaluation II score, Sequential Organ Failure Assessment score, C-reactive protein, absolute value lymphocyte count, serum albumin, white blood cell count, absolute value neutrophil count, secondary infection, and 28-day case fatality rate separately. Results: A total of 687 patients were admitted to the intensive care unit during the study period. The hospitalization time less than 14 days were excluded, and 168 patients were eventually included. There are 17 in the PICS group, 71 in the CCI group, 50 in the CCI + PICS group, and 30 in the NCCI + NPICS group. Baseline characteristics showed statistically significant differences in Sequential Organ Failure Assessment, length of hospital stay, and 28-day mortality among four groups. Baseline main indicator and multiple comparisons showed that the CCI + PICS group had longer hospital stay, worse prognosis, and more adverse outcomes. Multivariate analysis showed that final age, C-reactive protein on days 14 and 21, and serum albumin on days 1 and 21 had an impact on the prognosis ( P < 0.05). Conclusion: The clinical prognosis of the four groups decreased in order of NCCI + NPICS, CCI, PICS, and CCI + PICS. Our finding of clinically isolated PICS may indicate that PICS acts as an inducement or independent factor to worsen the prognosis of CCI.